Epidemiology and Outcome of Severe Sepsis and Septic Shock in Surgical Intensive Care Units in Northern Taiwan. Issue 47 (November 2015) - Huang, Chun-Ta; Tsai, Yi-Ju; Tsai, Pi-Ru; Yu, Chong-Jen; Ko, Wen-Je
Abstract : Abstract: Severe sepsis remains the leading cause of mortality in the critically ill. Local epidemiological studies on sepsis are of paramount importance to increase our knowledge about sepsis features and to improve patient care and prognosis. Adult patients (≥20 years) admitted to the surgical intensive care units with severe sepsis or septic shock from 2009 to 2010 were retrospectively retrieved and analyzed. The primary outcome of interest was 28-day mortality. Of 7795 admissions, 536 (6.9%) patients had severe sepsis. The most common sites of infection were the respiratory tract (38%) and abdomen (33%). Gram-negative bacteria, particularly Klebsiella pneumoniae (8.6%) and Escherichia coli (6.0%), were the major infecting micro-organisms, responsible for approximately two-thirds of the severe sepsis episodes. The overall 28-day mortality rate was 61%, and a higher sequential organ failure assessment score and the use of mechanical ventilation were independently associated with a worse outcome. Admissions with severe sepsis are not uncommon and are associated with substantial 28-day mortality in surgical intensive care units in northern Taiwan. Establishment and optimization of each institutional sepsis care standard to improve the outcome of sepsis are warranted.